Overview of Childhood Cancer- A cross-sectional study in Benghazi/Libya - Amal Elramli; Fatma Ben Khaial (Scientific Journal of University of Benghazi, 2018)
Child hood cancer which develop before 15 years of age are different from adult cancer in that it's not related to certain habits and environmental exposure that’s why we conduct this study to get an overview of these cancers in Benghazi. Our study concluded that there was a late diagnoses and resultant in poor outcome of childhood cancers in Benghazi therefore a necessitate national awareness of early diagnosis and optimal treatment.